Molecular characterisation of methicillin-resistant (MRSA) and methicillin-susceptible (MSSA) Staphylococcus aureus isolated from bovine subclinical mastitis and Egyptian raw milk cheese. (May 2020) - Zayda, Mahmoud Ge.; Masuda, Yoshimitsu; Hammad, Ahmed M.; Honjoh, Ken-ichi; Elbagory, Abdelrahman M.; Miyamoto, Takahisa
Abstract: We investigated the characteristics of Staphylococcus aureus isolates causing bovine subclinical mastitis (SCM), and their genetic relatedness with the isolates obtained from Egyptian cheese. Twenty-five S. aureus isolates were identified from 150 SCM milk and 75 cheese samples. The antibiogram revealed multidrug-resistant (MDR) isolates. Fifteen isolates were categorised as methicillin-resistant. Antimicrobial resistance and virulence genes were detected. Spa typing and SCC mec classification were performed. More than 50% of isolates were found carrying human-specific virulence determinants, while other isolates characterised were presumed to be of bovine-origin. Spa -types t304, t688, t084 corresponded isolates from SCM milk and cheese samples; the similar genotypes from SCM and cheese displayed divergence in virulence traits. Moreover, our results revealed the novel spa -type t18546. Animals and dairy food could be a reservoir for transformative changes in S. aureus virulence, leading to the emergence of virulent MDR strains that may become potential public-health threats.